Herbal Bioenhancers with Nanocarriers: A Promising Approach for Oral Peptide Delivery - Raghunath, Indu; Koland, Marina; Vadakkepushpakath, Anoop Narayanan; Kumar, Lalit; Shenoy, Sarathchandran Chandra Shekhar (International Journal of Pharmaceutical Investigation)
The oral delivery of protein and peptide drugs faces immense challenges due to the harsh gastrointestinal (GI) environment, large molecular size, and low stability. Even though different approaches are employed to deliver peptide drugs efficiently, they have limited success. Recently, the use of nanoparticles as carriers for peptides as a means of surmounting the gastrointestinal barrier and as an effective alternative to parenteral administration has gained much attention. It is often necessary to supplement this mode of delivery by using strategies such as permeation enhancers. Bio-enhancers play a significant role in reducing the dose, drug resistance, toxicity, and treatment expenses. The potential of herbal bio-enhancers as a safe and effective substitute to non-herbal permeation enhancers in improving oral absorption of peptides from nanoparticulate systems has been explored recently. Piperine is counted first in the list of bio-enhancers and can improve the bioavailability of peptides and other drugs. Other molecules like naringin, glycyrrhizin, quercetin have great significance either alone or in combination in improving the oral bioavailability of drug molecules. Bioenhancers are beneficial for drugs with poor lipid solubility and large molecular size, causing poor absorption and low bioavailability. Herbal bioenhancers can decrease the dose, drug resistance, toxicity, adverse effects, and overall treatment cost as they are inert, easily procured and economical. This review article focuses on the significance of nanoparticles in the oral delivery of peptide drugs and the vital role played by herbal bioenhancers in their absorption from the GI tract.
Keywords: Bio-enhancer; Herbal; Peptide drug; Nanoparticles; Bioavailability.